Efectuati calculele:
a) 2√6 + 3√3 * [ 8√3 - 2 * ( 4√3 -2√2 )] =
b) 50 + 2
√5 * [ 65√2 - 5(13√2 - 3√5)] =
c)12
√3 + 2 * { 20√2 - 2 * [ 18√3 - 5 * ( 3√3 - 2√2 )]} =
d) 90
√3 + 2√3 * { 18√2 - 3√3 * [ 8√6 - 3(2√6 - 5√3 )]} =

2
c. 12√3+2[20√2-2(3√3+10√3)]= 12√3+2(20√2-6√3-20√2)= 12√3+2(-6√3)=0

Răspunsuri

2014-02-11T09:05:15+02:00
Te ajut la a)!

2√6 + 3√3 *4√2 = 2√6 + 12√6 = 18√6;

Bafta!





Cel mai inteligent răspuns!
2014-02-11T10:26:52+02:00
A) 2√6+ 3√3*[8√3-2(4√3-2√2)= 2√6+3√3√*(8√3-8√3+4√2)=2√6+3√3( 8√3-8√3+4√2)=
2√6+3√3*4√2= 2√6+12√6=14√6

b)50+2√5*[65√2-5(13√2-3√5)=50+2√5(65√2-65√2+15√5)= 50+2√5*15√5= 50+30√25= 50+150= 200

1 5 1